Radio broadcasting for blacks during the Second World War : "It could be dangerous ..." (Historia, 2021)
One year after the Union of South Africa declared war on Germany in 1939, the South African government began to use radio broadcasting to a black target group as a medium for propaganda. In the winter of 1940, the Department of Native Affairs (DNA), responsible for transmitting propaganda to blacks, together with the South African Broadcasting Corporation (SABC) and the Department for Post and Telegraphs, launched the first broadcasting service for blacks in Johannesburg. The broadcast, which was initially only transmitted via telephone lines, differed considerably from the broadcast for whites. Based on extensive archival research, this article describes the conception and implementation of that broadcasting service along with the specific programming the DNA and the SABC introduced for black listeners. Because it includes enquiries on the reception of the service at that time, this article offers new insights into South African media history. The broadcasting service for blacks during the Second World War clearly reflected the white producers' stereotypical conception of blacks. It was designed to assert the hegemonic position of the white minority and legitimise and help to maintain the colonial order. However, the black audience did not prove to be the passive, grateful recipients of carefully selected information that producers expected them to be. Instead, several independent enquiries on audience response to the broadcasting service, for example from the Bantu News Service Committee of the Witwatersrand and the Sub-Committee of the South African Institute of Race Relations (SAIRR), suggested a rather critical response from the target audience.  Een jaar nadat die Unie van Suid-Afrika oorlog teen Duitsland verklaar het, het Suid-Afrika se regering begin om radio-uitsending as 'n medium vir propaganda na 'n swart teikengroet aan te wend. In die winter van 1940 het die Departement van Naturelle Sake (DNS), wat in beheer was van propaganda vir die swart bevolking, gepaard met die Suid-Afrikaanse Uitsaaikorporasie (SAUK) en die Departement Pos- en Telegraafdienste die eerste uitsaaidiens vir die Swart bevolking in Johannesburg van stapel gestuur. Die program, wat aanvanklik slegs via telefoonlyne versend is, het aansienlike van die programme vir witmense verskil. Gebaseer op uitvoerige argiefnavorsing, beskryf hierdie artikel die stigting en implementering van daardie uitsaaidiens gepaard met die spesifieke program die DNS en die SAUK wat vir swart luisteraars ingestel is. Insluitend navrae oor die ontvangs van die diens destyds, bied die artikel nuwe insigte in die Suid-Afrikaanse mediageskiedenis. Die uitsaaidiens vir swartmense tydens die Tweede WÃªreldoorlog weerspieÃ«l duidelik die wit aanbieders se stereotipe begrip van swartmense. Gevolglik het die diens die hegemoniese posisie van die wit minderheid onderhou en dus die koloniale orde in die gemeenskap geregverdig en meegehelp om dit te onderhou. Die swart luisteraars was egter nie die soort passiewe dankbare ontvangers van die geselekteerde inligting soos sommige aanbieders verwag het hulle sou wees nie. Inteendeel, etlike navra oor die ontvang van die uitsendingsdiens, byvoorbeeld by die Bantoe Nuusdienskomitee van die Witwatersrand of die Onderkomitee van die Suid-Afrikaanse Instituut van Rasseverhoudings (SAIRV), het op â??n heel kritiese respons van die luisteraars gedui.
Keywords: Racism; Suid-Afrikaanse Uitsaaikorporasie; Colonial order; Department of Native Affairs; Werwing; South African Broadcasting Corporation; Propaganda; Rasisme; Koloniale orde; Media history; Second World War; Radio; Departement Naturelle Sake; Mediageskiedenis; Segregasie; Tweede Wereldoorlog; Segregation